Me STUDI DESKRIPTIF FAKTOR PENYEBAB PERNIKAHAN DINI DI KECAMATAN PONDOK KELAPA KABUPATEN BENGKULU TENGAH: Judul Skripsi, Abstrak, Pendahuluan, Metodo Penelitian, Pembahasan dan Hasil, Kesimpulan - Wulan Puspita Sari; Rita Sinthia; Mayang T. Afriwilda (Consilia : Jurnal Ilmiah Bimbingan dan Konseling, 2023)
This study aims to describe the factors that cause early marriage in Pondok Kelapa District, Bengkul Tengah Regency. This research uses a quantitative descriptive method. The population in this study amounted to ± 200 respondents, the research sample was 36 respondents who were determined using purposive sampling technique. The data collection technique in this study used a guttman scale questionnaire and interviews as support. The results in the study of respondents who conducted early marriages that occurred in Pondok Kelapa District, Central Bengkulu Regency, from the six factors studied, there were four factors that caused early marriage, namely; economic factors, educational factors, parenting factors, and reproductive health knowledge. And there are two factors that do not cause early marriage, namely; mass media factors and cultural factors. Keywords: early marriage, causal factors, descriptive study